The History of Islamic Science and Its Characteristics: A Valuable Contribution to the Development of Islam in Modern Times - Badrun, Muhammad; Nasution, Alhafidh; Setiawan, Dandi; Ma'arif, Nizhof Lubbi (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
As a religion that encompasses comprehensive aspects of life, Islam has made important contributions to science throughout its history. The history of Islamic science dates back to the early Islamic enlightenment from the 7th to the 14th century AD. Strong emphasis was placed on the synthesis between science and religion. Scientific thinking and research were conducted with the understanding that knowledge of the universe was integral to an understanding of God's creation. Islamic science is characterised by an inclusive and multi-disciplinary approach. Muslim scholars of the time did not limit themselves to one particular field of science, but rather studied and developed knowledge in various disciplines such as mathematics, astronomy, medicine, physics, chemistry and philosophy. His valuable contributions to human civilisation. It also raises the question of how Muslims can combine the scientific heritage of Islam with the demands and challenges of the modern world, and how such a fusion can contribute to the sustainable and progressive development of Islam. As a result, the concept of Islamic science continues to be developed to this day.